The impact of item-writing flaws and item complexity on examination item difficulty and discrimination value. Issue 1 (December 2016) - Rush, Bonnie; Rankin, David; White, Brad
Abstract Background Failure to adhere to standard item-writing guidelines may render examination questions easier or more difficult than intended. Item complexity describes the cognitive skill level required to obtain a correct answer. Higher cognitive examination items promote critical thinking and are recommended to prepare students for clinical training. This study evaluated faculty-authored examinations to determine the impact of item-writing flaws and item complexity on the difficulty and discrimination value of examination items used to assess third year veterinary students. Methods The impact of item-writing flaws and item complexity (cognitive level I-V) on examination item difficulty and discrimination value was evaluated on 1925 examination items prepared by clinical faculty for third year veterinary students. Results The mean (± SE) percent correct (83.3 % ± 17.5) was consistent with target values in professional education, and the mean discrimination index (0.18 ± 0.17) was slightly lower than recommended (0.20). More than one item-writing flaw was identified in 37.3 % of questions. The most common item-writing flaws were awkward stem structure, implausible distractors, longest response is correct, and responses are series of true-false statements. Higher cognitive skills (complexity level III-IV) were required to correctly answer 38.4 % of examination items. As item complexity increased, item difficulty and discrimination values increased. The probability of writing discriminating, difficult examination items decreased when implausible distractors and all of the above were used, and increased if the distractors were comprised of a series of true/false statements. Items with four distractors were not more difficult or discriminating than items with three distractors. Conclusion Preparation of examination questions targeting higher cognitive levels will increase the likelihood of constructing discriminating items. Use of implausible distractors to complete a five-option multiple choice question does not strengthen the discrimination value.